Achieving cooler soil as an effective heat sink for earth-to-air heat exchanger(EAHE)cooling technology in Malaysia tropical climate - Sanusi, Aliyah Nur Zafirah; Ahmad Zamri, Aidil Azlan (Scientific Research Publishing, 2014)
This research is intended to explore the capacity of Malaysia soil in becoming a more effective heat sink for the application of Earth-to-Air Heat Exchanger(EAHE)Cooling Technology in Malaysia. EAHE Cooling Technology consists of buried pipes underground where the ambient air is channeled through from the pipe inlet and produces cooler air at its outlet. Within the buried pipes, heat exchange process occurs between the air and the soil that surrounding the pipe. This building cooling technology has been applied in many countries, mostly in temperate or hot and arid climate where the diurnal temperature is large. However, minimal resources were found on the study of EAHE application to buildings in Malaysia, hence there is room to develop. A parametric study on EAHE cooling application in Malaysia was done through field experiment and concluded that among many parameters affecting the technology performance, the soil temperature which surrounded the pipe was the most influential factor. The study recommended to further reduce the soil temperature to achieve a cooler outlet temperature. In response to that, this research conducted a parametric study of soil temperature under three different soil surface conditions; bare, shaded with timber pallettes and insulated with used tyres at 1.0m and 1.5m underground. The data was logged for a month and the result has shown significant reduction in the soil temperature underground below the shaded and insulated soil surface as compared to below bare soil surface condition. The insulated soil surface produced the best result where the soil temperature was reduced up to 26.9̊C. The main contribution of this paper is to highlight that the soil surface treatment can be used to reduce solar heat gain within the soil underground and thus improving the performance of EAHE Cooling Technology particularly for the application in Malaysia tropical climate.